2018
DOI: 10.1590/s1983-41952018000100005
|View full text |Cite
|
Sign up to set email alerts
|

Fresh and hardened properties of self-compacting concrete modified with lightweight and recycled aggregates

Abstract: A produção de concretos auto compactáveis de baixa massa específica tornou-se um grande desafio para a engenharia civil, principalmente quanto à dosagem e manutenção das resistências mecânicas. Nesse contexto, o objetivo deste trabalho foi analisar concretos autoadensáveis (CAA) produzidos com agregados leves e reciclados. Fixou-se as dosagens de sílica ativa, pó de pedra, pedrisco, argila expandida e superplastificante, variando-se a porcentagem do resíduo de borracha em 5% e 10%, em substituição ao agregado … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 16 publications
2
3
0
1
Order By: Relevance
“…The SCC/10SF/30MGR/2.5R mixture has shown a 14.5% reduction in the compressive strength when compared with the SCC/10SF sample. The decrease in compressive strength with the increase of rubber content is also previously reported [16,37,39,[64][65][66]. This occurrence is attributed to two main reasons: (a) firstly, the cracks are rapidly initiated at neighboring the rubber particles and concrete paste, and (b) the rubber particles are weakly adhered to the paste, behaving like voids in the concrete matrix [16,64].…”
Section: Hardened State Propertiessupporting
confidence: 77%
See 1 more Smart Citation
“…The SCC/10SF/30MGR/2.5R mixture has shown a 14.5% reduction in the compressive strength when compared with the SCC/10SF sample. The decrease in compressive strength with the increase of rubber content is also previously reported [16,37,39,[64][65][66]. This occurrence is attributed to two main reasons: (a) firstly, the cracks are rapidly initiated at neighboring the rubber particles and concrete paste, and (b) the rubber particles are weakly adhered to the paste, behaving like voids in the concrete matrix [16,64].…”
Section: Hardened State Propertiessupporting
confidence: 77%
“…Similarly when the SCC/20SF/30MGR/5R and the SCC/20SF samples are also compared. In previous studies this behavior is also reported [16,23,[64][65]. From this point, it is important to remark the decision to rubber content be adopted in the proposed mixture examined in the present investigation.…”
Section: Hardened State Propertiessupporting
confidence: 77%
“…By the chemical characterization it was observed the presence of 76.34% of SiO 2 and 12.49% of CaO in the ornamental rock waste, close to those found in the literature [16,[44][45][46], while lime is mostly composed of CaO, around 93.43%. In the mineralogical analysis of ornamental rock waste, the predominant minerals were quartz and dolomite, showing good correlation between the chemical analysis performed and studies previously carried out on these materials [8,12,18,20,24,45]. Lime is predominantly composed of portlandite and calcite [46].…”
Section: Chemical and Microstructural Characterizationmentioning
confidence: 60%
“…The rock beneficiation process is divided into two stages: the blocks extraction and their beneficiation. According to Angelin et al [12], in this last stage, the waste generation can reach 20 to 30% of the block volume. Furthermore, during the extraction of marble and granite, the loss can reach 60%, and this activity produces a fine dust that can cause health problems and damage the soil [10,11,13].…”
Section: Introductionmentioning
confidence: 99%
“…The rubber residue from waste tires has important physical and mechanical characteristics, which make it strongly recommended to be used in civil construction in concrete [14][15][16][17][18] and mortar [19][20][21][22] . Seeking to mitigate the harmful effects of its disposal on the environment 23 .…”
Section: Literature Reviewmentioning
confidence: 99%